Plant-based meats: alternative source of protein or yet another ultra-processed food option? (Simbiótica. Revista Eletrônica, 2025)
Due to its high ecological footprint, the animal protein production sector is considered unable to sustainably meet the global demand for protein. This scenario has driven a transition toward diets with lower meat consumption and a greater presence of plant-based foods. Plant-based meats have emerged as promising alternatives, with the potential to reduce environmental impacts, prevent animal suffering, and promote human health. However, the lack of consolidated information on their composition, nutritional value, and actual benefits raises questions about their effects on human health and the environment. Based on a systematic review of documents published between 2006 and 2023, this article analyzes the narrative disputes surrounding the ability of these products to safely and sustainably meet the growing demand for quality protein.
Keywords: Meat substitutes; Narratives; Food safety; Ultra-processed food